Understanding Consumer Purchase Intention for Halal Cosmetics: Product Quality, Halal Label and Celebrity Endorser - Shelma Kharami; Faizatul Hiqmah (Sekolah Tinggi Manajemen IPMI, 2023)
The purpose of this study is to analyze and examine the effect of product quality, halal label, and celebrity endorser on consumer purchase intention for halal-labeled cosmetics in East Java. The subjects of this study are Muslim women in East Java. This study uses primary data collected using purposive sampling technique and involves a sample of 110 Muslim women who live in various areas in East Java. The variables used in this study are the dependent variable of purchase intention and the independent variables of product quality, halal label, and celebrity endorser. The results of this study show that product quality and halal label have a significant positive effect on the purchase intention for halal cosmetics, while celebrity endorser has an insignificant positive effect on the purchase intention for halal cosmetics.